PENGARUH RASIO LIKUIDITAS, PROFITABILITAS, DAN SOLVABILITAS TERHADAP NILAI PERUSAHAAN DENGAN HARGA SAHAM VARIABEL INTERVENING PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PADA TAHUN 2020-2023 - Istifaza, Zulfa; Subaida, Ida; Fandiyanto, Randika (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
Food and beverage companies listed on the Indonesia Stock Exchange are one of the manufacturing industries that continue to experience growth, mainly because food and beverages are basic human needs. This industry is important in meeting consumer needs and contributing to economic growth. This study aims to analyze the effect of Liquidity, Profitability, and Solvency ratios on Company Value with Stock Price as an intervening variable. The Liquidity ratio is measured by the Current Ratio (CR), the Profitability ratio is measured by the Return on Assets (ROA), and the Solvency ratio is measured by the Debt to Equity Ratio (DER). The company value is measured by the Price to Book Value (PBV). At the same time, the Stock Price is used as an intervening variable to see how much the relationship between these financial ratios affects the Company Value. The method used in this study is a quantitative method with a descriptive approach. The research sample consists of nine companies engaged in the food and beverage sector listed on the IDX and meets the criteria determined by the sampling technique, namely purposive sampling. The data used is secondary data obtained from the company’s annual financial reports published on the Indonesia Stock Exchange website. The data analysis technique used is Structural Equation Modeling (SEM) with the help of the Smart PLS application. The results of the direct influence hypothesis test using the Smart PLS application show that Liquidity, Profitability, and Solvency have no significant effect on Stock Price. Liquidity and Solvency have no significant effect on Company Value. Yet, Profitability has a significant effect on Company Value. The indirect influence hypothesis test results show that Liquidity, Profitability, and Solvency on Company Value through Stock Price have no significant effect.